2014
DOI: 10.5694/mja14.00019
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary arrest and mortality trends, and their association with rapid response system expansion

Abstract: During nearly a decade, as RRSs were progressively introduced, there was a coincidental reduction in IHCA, IHCA-related deaths and hospital mortality and an increased survival to hospital discharge after an IHCA. Reduced IHCA incidence, rather than improved postcardiac arrest survival, was the main contributor to the reduction in IHCA mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 25 publications
3
59
0
2
Order By: Relevance
“…218 The other study demonstrated a significant difference between control wards and intervention wards (introduction of a critical care outreach service) with all patients (OR, 0.70; 95% CI, 0.50-0.97), and matched randomized patients (OR, 0.52; 95% CI, 0.32-0.85). 219 Of the 33 nonrandomized studies reporting mortality, no studies reported statistically significant worse outcomes for the intervention; 15 studies with no adjustment demonstrated no significant improvement [220][221][222][223][224][225][226][227][228][229][230][231][232][233][234] ; 6 studies with no adjustment demonstrated significant improvement [235][236][237][238][239][240] ; 1 study with no adjustment reported on rates, which improved with MET, but did not report on significance 241 ; 1 study with no adjustment demonstrated significant improvement for medical patients but not surgical patients (combined significance not reported) 242 ; 4 studies with adjustment demonstrated significant improvement both before and after adjustment 243,244,250,252 ; 2 studies with adjustment demonstrated no significant improvement both before and after adjustment 245,246 ; 2 studies with adjustment demonstrated significant improvement before adjustment but not after adjustment 247,251 ; 1 study with adjustment demonstrated significant improvement before adjustment but not after adjustment 27 ; 1 study that reported on both unexpected mortality and overall mortality showed significant improvement both before and after adjustment for unexpected mortality but no significant improvement both before and after adj...…”
Section: Consensus On Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…218 The other study demonstrated a significant difference between control wards and intervention wards (introduction of a critical care outreach service) with all patients (OR, 0.70; 95% CI, 0.50-0.97), and matched randomized patients (OR, 0.52; 95% CI, 0.32-0.85). 219 Of the 33 nonrandomized studies reporting mortality, no studies reported statistically significant worse outcomes for the intervention; 15 studies with no adjustment demonstrated no significant improvement [220][221][222][223][224][225][226][227][228][229][230][231][232][233][234] ; 6 studies with no adjustment demonstrated significant improvement [235][236][237][238][239][240] ; 1 study with no adjustment reported on rates, which improved with MET, but did not report on significance 241 ; 1 study with no adjustment demonstrated significant improvement for medical patients but not surgical patients (combined significance not reported) 242 ; 4 studies with adjustment demonstrated significant improvement both before and after adjustment 243,244,250,252 ; 2 studies with adjustment demonstrated no significant improvement both before and after adjustment 245,246 ; 2 studies with adjustment demonstrated significant improvement before adjustment but not after adjustment 247,251 ; 1 study with adjustment demonstrated significant improvement before adjustment but not after adjustment 27 ; 1 study that reported on both unexpected mortality and overall mortality showed significant improvement both before and after adjustment for unexpected mortality but no significant improvement both before and after adj...…”
Section: Consensus On Sciencementioning
confidence: 99%
“…220,221,224,225,[227][228][229][230][232][233][234][235][236][237][238][239][240][241][242][243][244][245][246][247]249,250,[253][254][255][256] For the 1 RCT, 218 no significant difference between control hospitals and intervention hospitals, both unadjusted (P=0.306; Diff, −0.208; 95% CI, −0.620 to 0.204) and adjusted (P=0.736; OR, 0.94; 95% CI, 0.79-1.13), was demonstrated. Of the 31 observational studies reporting on cardiac arrest rates, 1 before-after study using an aggregated weighted scoring system (Modified Early Warning Score [MEWS]) reported significantly higher cardiac arrest rates in MEWS bands 3 to 4 after intervention, but not in MEWS bands 0 to 2 or 5 to 15, and overall cardiac arrest rate significance was not reported 232 ; 7 studies with no adjustment demonstrated no significant improvement in cardiac arrest rates after the introduction of a MET system 224,225,[228][229][230]233,234 ; 15 studies with no adjustment demonstrated significant improvement in cardiac arrest rates after the introduction of a MET system 220,221,…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Results of earlier studies in terms of hospital mortality were conflicting, with several studies [8,14], [17][18][19][20][21][22][23] showing a reduction and others [9,11,13,[24][25][26][27][28] showing no change or even an increase [29] in hospital mortality following rapid response system implementation. A systematic review and meta-analysis from Chan et al [11] did not demonstrate any overall benefit from rapid response systems in terms of hospital mortality (pooled RR = 0.96 [0.84-1.09]) with a significant heterogeneity of results (I 2 = 90.3%; p < 0.001).…”
Section: Hospital Mortalitymentioning
confidence: 95%
“…In 2014, Chen and colleagues [65] analyzed data of 9,221,138 patients of 82 public acute hospitals, in New South Wales, in Australia (Table IV).…”
Section: Population-based Studiesmentioning
confidence: 99%